MEMBACA KEMAMPUAN MENULIS PROPOSAL SKRIPSI PADA MAHASISWA: JALAN PANJANG MEMBANGUN LITERASI BANGSA - Mustikasari, Molly; Marlida, Siti; Ma'shum, Muhammad Zuhdy (FASTABIQ: JURNAL STUDI ISLAM, 2023)
The purpose of this study is to determine the ability of students in making thesis proposals. The identification of the ability to make a thesis proposal is expected to improve students' weaknesses in writing thesis proposals.  This research was conducted to students who have taken research methodology courses at the Faculty of Islamic Religion, Universitas Muhammadiyah Bandung.  The research method used was descriptive qualitative. The sample was 30 students who were taken purposively. Data in the form of thesis proposals in research methodology courses were analysed using research instruments in the form of thesis proposal writing structure tables and using descriptive statistical data to help interpret the data.  The results showed that in the ability to write proposals, showing the making of titles in the "Good" category. Background writing is in the "Fair" category. The writing of the problem formulation is in the "Good" category. While writing the theory and literature review falls into the "Fair" category, as well as the research method falls into the "Fair" category.Keywords : Writing competency; writing scientific paper; writing literacy